Cloud logistics and risk assessment design platform based on service modularisation. (8th June 2021) - Shen, Yuyan; Qian, Yan; Li, Shufang; Wu, Xudong
This paper is intended to develop a cloud logistics service model from the three dimensions of service modularisation, namely design structure, interface and standards. A case study research method was employed to analyse the service modularisation of Star Express's cloud logistic platform based on service process modularisation, service function modularisation and service object modularisation and to propose the realisation method of the modularisation service mode of the logistics service of the e-commerce platform. Further, this study conducted a risk assessment of the modularisation service quality of the cloud logistics platform, through the cloud logistics platform risk assessment model based on the OWA operator. Research findings revealed that cloud logistics service model and risk assessment analysis leads to decreasing the maintenance costs, and improves the service quality and optimise the modularisation service of the cloud logistics platform.